Rotavirus in Calves and Its Zoonotic Importance - Umer Seid Geletu; Munera Ahmednur Usmael; Fufa Dawo Bari (Veterinary Medicine International)
Rotavirus is a major pathogen responsible for diarrheal disease in calves, resulting in loss of productivity and economy of farmers. However, various facets of diarrheal disease caused by rotavirus in calves in the world are inadequately understood, considering that diarrheal disease caused by rotavirus is a vital health problem in calves that interrupts production benefits with reduced weight gain and increased mortality, and its potential for zoonotic spread. The pathological changes made by rotavirus are almost exclusively limited to the small intestine that leads to diarrhea. It is environmentally distributed worldwide and was extensively studied. Reassortment is one of the important mechanisms for generating genetic diversity of rotaviruses and eventually for viral evolution. So, the primary strategy is to reduce the burden of rotavirus infections by practicing early colostrum’s feeding in newborn calves, using vaccine, and improving livestock management. Rotaviruses have a wide host range, infecting many animal species as well as humans. As it was found that certain animal rotavirus strains had antigenic similarities to some human strains, this may be an indication for an animal to play a role as a source of rotavirus infection in humans. Groups A to C have been shown to infect both humans and animals. The most commonly detected strains in both human and animals are G2, G3, G4, and G9, P [6]. Therefore, this review was made to get overview epidemiology status and zoonotic importance of bovine rotavirus.